2019
DOI: 10.1063/1.5081804
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphic MEMS sensor network

Abstract: This work investigates the computational potential of microelectromechanical system (MEMS) networks. In these networks, each MEMS device retains the memory of past inputs through bistability and hysteresis and receives a weighted excitatory or inhibitory feedback from other devices within the network. These interactions are shown to change the dynamics of a small network of MEMS devices to produce selective switching and limit cycles through Hopf bifurcations. Furthermore, we show that interactions within larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…While previous works have shown the potential of performing simple edge computing using MEMS sensors [43], this approach shows a new generation of intelligent sensors can be produced without using large networks of sensory elements [44]. Such sensors will entirely utilize transience, increasing their speeds.…”
Section: Discussionmentioning
confidence: 95%
“…While previous works have shown the potential of performing simple edge computing using MEMS sensors [43], this approach shows a new generation of intelligent sensors can be produced without using large networks of sensory elements [44]. Such sensors will entirely utilize transience, increasing their speeds.…”
Section: Discussionmentioning
confidence: 95%
“…To overcome the challenges, in previous work, we have identified nonlinearity and hysteresis as essential properties for CTRNNs to perform computing. Thus, we have shown that systems exhibiting these properties, such as a network of coupled bi-stable MEMS devices, are candidates for performing CTRNN computing in an analog fashion [ 12 , 13 ]. However, while that work demonstrated an efficient way to perform CTRNN computing using MEMS devices, it followed a typical machine learning structure that separates the input (sensor) layer from the computing layer ( Figure 3 a).…”
Section: Theory and Methodologymentioning
confidence: 99%
“…In our previous work, we presented the novel use of MEMS electrostatic sensor dynamics with special geometric nonlinearities to naturally solve the continuous-time recurrent neural network (CTRNN) equations [ 12 , 13 ]. In that implementation, there is no need for a digital computer to solve the CTRNN equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work (26) Alternative means of employing MEMS devices for CTRNN include using MEMS structures with nonlinear geometries, such as MEMS arches, and using internal feedback by using electrical resonance in low parasitic capacitance MEMS devices. For simplicity, this work focuses on using electrostatic MEMS devices, operated in the pull-in/release regime (5) to construct a MEMS CTRNN.…”
Section: Mems-ctrnn Model Architecturementioning
confidence: 99%